Flexible and focused: the experience of Poly Glass Fibre (M) Berhad - Basri, Syazwan; Mhd. Sarif, Suhaimi (Meso Publishing, 2016)
This book shares the research findings of Advanced Corporate Strategy course on the practical experience of corporate strategy at Poly Glass Fibre (M) Berhad. This company is listed as Shariah compliant equity with Bursa Malaysia. The main business strategy is focused differentiation in ecowool glass fibre. With its Shariah compliant equity status, this company managed to grow domestically and regionally.